ONLINE VS TRADITIONAL; MARKETING CHALLENGE IN THE TELECOM MARKET IN BOSNIA AND HERZEGOVINA - Tarik Zaimović; Adnan Suturović (Economic Review)
Understanding consumer behavior in media advertising enables companies to effectively direct marketing activities toward the target market. Today, companies are expected to continually communicate with current and potential customers. Although online advertising methods are a relatively new concept compared to the established traditional ways of advertising, integrated marketing communication consists of messages sent to consumers using a set of various marketing instruments. The results of our research have shown that the users of telecommunication services in Bosnia and Herzegovina (BiH) pay more attention to the marketing messages sent over the online media. Social networks are the marketing communication medium preferred by most of the telecomm users in BiH, followed by television, billboards, text messages, company web page, web advertisements, newspapers, e-mail, and the radio. The results presented in this paper consider consumers’ behavior in one of the most dynamic BiH sectors, and provide an insight in the specific media channel of marketing communication.